Deterioration of pulmonary hypertension and pleural effusion with bosutinib following dasatinib lung toxicity. Issue 5 (6th October 2016) - Riou, Marianne; Seferian, Andrei; Savale, Laurent; Chaumais, Marie-Camille; Guignabert, Christophe; Canuet, Matthieu; Magro, Pascal; Rea, Delphine; Sitbon, Olivier; Jaïs, Xavier; Humbert, Marc; Montani, David
Tyrosine kinase inhibitors (TKIs) targeting BCR/ABL such as imatinib, nilotinib, dasatinib, bosutinib and ponatinib have revolutionised the management of patients with chronic myeloid leukaemia (CML) [1]. Pleural effusions and pulmonary arterial hypertension (PAH) have been reported in patients treated with these agents [2–4]. These side-effects are more frequently observed with dasatinib use, with partial or complete reversibility after drug withdrawal [3]. Bosutinib is a second-generation TKI prescribed in case of intolerance or resistance to imatinib, nilotinib or dasatinib. In the present report, we describe two cases of worsening of dasatinib-induced PAH and two cases of severe pleural effusions, suggesting overlapping pulmonary toxicity of bosutinib and dasatinib. Pulmonary complications of bosutinib therapy and potential cross-intolerance with dasatinib http://ow.ly/UKWu303KGhx